INDUSTRIALISASI DAN EKSISTENSI KOTA LANGSA PADA ERA KOLONIAL, 1907-1942 - Muhajir, Ahmad; Yuliati, Dewi; Rochwulaningsih, Yety (Paramita: Historical Studies Journal, 2017)
This study aimed to examine the existence of Langsa as a colonial city during the first half of the 20th century, which focused on development of capitalism in industrial sector and its relation with establishment of this city. Colonial government had to developed capitalism through industrialization and to accommodated the private interests. East Aceh previously had a traditional economic-base on pepper agriculture but this was devastated by war and then replaced by capitalism. Industrialization was implemented by the Dutch on transportation, communication, public services and rubber plantation industries. Then the private capitalists were dominated the rubber plantation and petroleum mining industries. Industrialization was the determinant factor of the growth of Langsa as the colonial city and impacted the major changes and development of urban space. Since 1907, Langsa became the third largest city in Aceh until the end of the Dutch colonialism in 1942.Â Studi ini bertujuan untuk mengkaji eksistensi Langsa sebagai kota kolonial pada paruh pertama abad ke-20, yang difokuskan pada perkembangan kapitalisme di sektor industri dan hubungannya dengan pembangunan kota tersebut. Pemerintah kolonial didorong untuk mengembangkan kapitalisme melalui industrialisasi untuk mengakomodir kepentingan kapitalis swasta. Dahulu Aceh Timur memiliki basis ekonomi tradisional pada pertanian lada namun hancur akibat perang dan kemudian digantikan oleh kapitalisme. Industrialisasi diimplementasikan oleh Belanda pada industri jasa transportasi, komunikasi, layanan umum dan perkebunan karet. Kemudian industri perkebunan karet dan pertambangan minyak bumi didominasi oleh kapitalis swasta. Industrialisasi merupakan faktor determinan pertumbuhan Langsa sebagai kota kolonial dan berdampak pada perubahan besar dan perkembangan ruang kota. Hanya satu dasawarsa (1907-1917), Langsa telah menjadi kota ketiga terbesar di Aceh hingga akhir kolonialisme Belanda pada tahun 1942.Â